[Portrait of Phillip Adams, addressing the National Press Club, Canberra, 26 July 1989] - National Library of Australia (1989)
Phillip Adams is a writer, journalist, film producer and radio broadcaster. He was chairman of the Australian Film Commission from 1985 to 1990.
Title devised by cataloguer from information on negative packet.
Condition good.
Negative to be found in packet (2) of 2 packets (1 & 2).
Part of a collection of photographs of Phillip Adams addressing the National Press Club, Canberra, 26 July 1989.
Also available online
National Library of Australia Oral History section ORAL TRC 4119
Keywords: Adams, Phillip, -- 1939- -- Portraits; Journalists -- Australia -- Portraits; Motion picture producers and directors -- Australia -- Portraits; Radio broadcasters -- Australia -- Portraits; Authors, Australian -- Portraits; Film producers and directors; Broadcasters; Authors; Journalists